Deconvolution of complex crystallization processes: Amorphous selenium - Svoboda, Roman; Málek, Jiří (University of Pardubice, 2012)
Crystallization behavior of the selenium glass was studied by means of the differential scanning calorimetry under non-isothermal conditions. Two new approaches to the evaluation of crystallization kinetics — advanced interpretation of characteristic kinetic functions and modified Fraser–Suzuki deconvolution — were applied. The determination of kinetic parameters in the dependence on particle size can provide an extensive amount of information about the nature of the involved surface and bulk crystallization mechanisms. Based on these information, the deconvolution in terms of the Johnson–Mehl–Avrami process was performed, separating the two mechanisms. The results not only both, qualitatively and quantitatively, describe the crystallization process in glassy selenium but also explain various data from literature on this topic. Introduced deconvolution may represent a new approach to gaining information about complex crystallization processes for numerous material science applications.